The Golomang Tradition in the Funeral Procession in Bolaang Mongondow from the Perspective of Islamic Law - Madinah mokobombang; Candra Kirana Putri Calya Candra Kirana (Indonesian Civil Law Review, 2026)
This research is motivated by the people of Bolaang Mongondow, particularly in Otam Village, Bilalang Village, and Pangian Village, who continue to preserve the Golomang Tradition (Kolintang), as well as its conformity with Islamic law. This study aims to examine the procedures for carrying out the Golomang Tradition in mourning processions and to analyze it from the perspective of Islamic law. This research employs a qualitative method with sociological and normative approaches. The data sources were obtained from religious leaders, traditional leaders, and community members through observation, interviews, and documentation. The results of the study show that the Golomang Tradition is performed at several stages of mourning, namely after the arukus has been erected, after the body has been washed, before the remarks from village officials, when the body is about to be taken to its final resting place, and on the third, seventh, and fourteenth nights after the recitation of prayers. This tradition is understood by the community as a form of final respect and as a means of strengthening social solidarity. From the perspective of Islamic law, this practice does not contradict Islamic teachings as long as it does not contain elements of deviant belief and remains within the boundaries of permissible custom (‘Urf Shahih). Therefore, the Golomang Tradition can be positioned as a cultural custom that exists alongside the implementation of Islamic law in funeral rites.